Flipped Classroom in Islamic Education: A Systematic Review of Pedagogical Impact at Junior and Senior High School Levels - Syamsudin, Ahmad; Rofiani Rofiani; Andriyana Andriyana; Zul Andrivat; Azizah Nur Islami (PT. Banjarese Pacific Indonesia, 2025)
The flipped classroom model has increasingly been implemented as an alternative instructional approach in the digital era, including in Islamic Religious Education (IRE) at junior and senior high school levels. This article aims to systematically examine eight empirical publications from 2021 to 2025 that explore the application of this model within IRE contexts. The review focuses on instructional design, pedagogical outcomes, and implementation challenges. Findings from the analyzed studies suggest that applying the flipped classroom model in IRE can enhance students’ cognitive understanding, foster learning motivation, and develop critical and collaborative thinking skills. However, the effectiveness of this model depends heavily on the quality of digital learning design, the teacher’s readiness to facilitate active learning, and the ability to meaningfully integrate Islamic values into the learning process. In addition, this model faces several challenges, including limitations in technological infrastructure, lack of professional teacher training, and the need for curriculum adaptation. This study highlights the importance of systemic support and digital competency development among educators to ensure that flipped classroom implementation is not merely a technical strategy, but a means of strengthening the spiritual dimension and core values of Islamic education in the digital age.